Advanced oxidation process-mediated removal of pharmaceuticals from water: A review. (1st August 2018) - Kanakaraju, Devagi; Glass, Beverley D.; Oelgemöller, Michael
Abstract: Pharmaceuticals, which are frequently detected in natural and wastewater bodies as well as drinking water have attracted considerable attention, because they do not readily biodegrade and may persist and remain toxic. As a result, pharmaceutical residues pose on-going and potential health and environmental risks. To tackle these emerging contaminants, advanced oxidation processes (AOPs) such as photo-Fenton, sonolysis, electrochemical oxidation, radiation and ozonation etc. have been applied to remove pharmaceuticals. These processes utilize the high reactivity of hydroxyl radicals to progressively oxidize organic compounds to innocuous products. This review provides an overview of the findings from recent studies, which have applied AOPs to degrade pharmaceutical compounds. Included is a discussion that links various factors of TiO2 -mediated photocatalytic treatment to its effectiveness in degrading pharmaceutical residues. This review furthermore highlights the success of AOPs in the removal of pharmaceuticals from different water matrices and recommendations for future studies are outlined. Highlights: WWTPs remain the main route for pharmaceuticals to the environment. Hybrid AOPs offer better API mineralization and as a consequence improve the quality of effluents. Complexity of water matrices dictate the efficiency of AOPs to degrade pharmaceuticals. Real wastewater matrices should be a focus of TiO2 photocatalytic oxidation.